2023
DOI: 10.1515/nanoph-2022-0594
|View full text |Cite
|
Sign up to set email alerts
|

Electrically tunable conducting oxide metasurfaces for high power applications

Abstract: Active metasurfaces designed to operate at optical frequencies are flat optical elements that can dynamic, subwavelength-scale wavefront control of reflected or transmitted light. The practical and fundamental power-handling limits of active metasurfaces at high pulse energies and high average powers determine the potential applications for these emerging photonic components. Here, we investigate thermal performance limits of reflective gate-tunable conducting oxide metasurfaces illuminated with high power den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Moreover, the large transparency window of BTO and the freedom to structure it on transparent insulating substrates enables to utilize the NUV and VIS spectrum range with minimized damage from absorption at high optical powers. The increased field in the electro‐optic medium or in the nanohole cavities can be particularly beneficial for high‐speed beam steering metasurfaces [ 43 ] or advanced nanohole array sensors. [ 31 ] This high‐throughput fabrication platform is advantageous for improving the fabrication flexibility required for application optimized nonlinear photonic devices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the large transparency window of BTO and the freedom to structure it on transparent insulating substrates enables to utilize the NUV and VIS spectrum range with minimized damage from absorption at high optical powers. The increased field in the electro‐optic medium or in the nanohole cavities can be particularly beneficial for high‐speed beam steering metasurfaces [ 43 ] or advanced nanohole array sensors. [ 31 ] This high‐throughput fabrication platform is advantageous for improving the fabrication flexibility required for application optimized nonlinear photonic devices.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is shown that the interelement coupling between the adjacent unit cells is significant under TM polarization in comparison to TE, which leads to cross talk and undesired sidelobes 73 75 …”
Section: Ultrahigh Q-factor Resonant All-dielectric Metasurfacementioning
confidence: 99%
“…However, it is shown that the interelement coupling between the adjacent unit cells is significant under TM polarization in comparison to TE, which leads to cross talk and undesired sidelobes. [73][74][75] In order to get better insight into the radiative properties of the resonant modes, we employ the multipole decomposition up to the fourth order, tied by electric and magnetic octupoles, to calculate the contribution of each multipole in the scattering response. For this purpose, we have conducted a theoretical analysis based on multipole decomposition method developed for light scattering.…”
Section: Ultrahigh Q -Factor Resonant All-dielectric Metasurfacementioning
confidence: 99%
“…2,8 Electrically tunable metasurfaces have attracted particular attention because they can be readily integrated with existing optoelectronic devices, exploiting the technical maturity of the modern electronics industry. [9][10][11][12][13] Recently, highly conductive poly(3,4-ethylenedioxythiophene) (PEDOT) based polymer nanoantennas have shown unique potential as a building block of electrically tunable metasurfaces working in the infrared spectral range. [14][15][16][17][18][19] Therein, the redox states of the PEDOT nanoantennas were controlled by electrochemical doping and dedoping, resulting in changes in both charge carrier concentration and mobility, and consequently nanooptical responses.…”
Section: Introductionmentioning
confidence: 99%
“…2,8 Electrically tunable metasurfaces have attracted particular attention because they can be readily integrated with existing optoelectronic devices, exploiting the technical maturity of the modern electronics industry. 9–13…”
Section: Introductionmentioning
confidence: 99%